2016
DOI: 10.1136/jim-2016-000081
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 4-1Bb and Its Ligand on Blasts Correlates with Prognosis of Patients with Aml

Abstract: Costimulatory ligands (COLs) and their receptors (COR) regulate immune reactions and cellular survival and might be relevant in acute myeloid leukemia (AML). This study evaluated the clinical relevance of 4-1BBL, glucocorticoid-induced TNFR-related protein (GITR) and ligand (GITRL), CD80, and CD86 in case of expression on AML blasts. 98 patients were evaluated at initial diagnosis. Immunophenotypically evaluated specific fluorescence index (SFI) levels of COR and COL on blasts were correlated with morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
(94 reference statements)
1
3
1
Order By: Relevance
“…This is supported by our finding that patients with high 4-1BB expression on CLL B cells have a shorter OS. This is in contrast to data on 4-1BB on AML blasts [47] and might be explained by the different disease biology.…”
Section: Discussioncontrasting
confidence: 99%
“…This is supported by our finding that patients with high 4-1BB expression on CLL B cells have a shorter OS. This is in contrast to data on 4-1BB on AML blasts [47] and might be explained by the different disease biology.…”
Section: Discussioncontrasting
confidence: 99%
“…As previously reported, CD80 and CD86 expression in group I of the B7 family on AML blasts do not exhibit significant prognostic relevance (31), while ICOSL expression in AML cells influences survival by driving regulatory T cells expansion (11). In AML patients, an association was identified between highly expressed PD-L1, PD-L2, and PD-1 in group II of the B7 family and poor OS (32).…”
Section: Discussionsupporting
confidence: 56%
“…Of note, one study reported that the expression of 41BBL could predict patient outcome in acute myeloid leukemia. 42 Our work revealed that PD1, 41BB/41BBL, TIM3, and LAG3 are crucial checkpoints on γδT cells allowing immune escape and tumor progression. These observations thus pointed out that γδT cells may be interesting cells to look at in the context of current immunotherapies with immune checkpoint blockers, as they displayed a perturbed immune checkpoint panel expression and could be targeted by these therapies.…”
Section: Discussionmentioning
confidence: 69%